Killer-cell immunoglobulin-like receptor gene 3DL1*077 isolated using long-range sequence-based techniques. - Yindom, L; Wang, L; Rowland-Jones, S; Dong, T (2014)
KIR3DL1*077 gene has two non-synonymous mutations (exon 5) and six intronic changes compared to KIR3DL1*0150201.